Representations of Transnational Human Trafficking Present-day News Media, True Crime, and Fiction - Gregoriou, Christiana (Springer Nature, 2018)
This open access edited collection examines representations of human trafficking in media ranging from British and Serbian newspapers, British and Scandinavian crime novels, and a documentary series, and questions the extent to which these portrayals reflect the realities of trafficking. It tackles the problematic tendency to under-report particular types of victim and forms of trafficking, and seeks to explore both dominant and marginalised points of view. The authors take a cross-disciplinary approach, utilising analytical tools from across the humanities and social sciences, including linguistics, literary and media studies, and cultural criminology. It will appeal to students, academics and policy-makers with an interest in human trafficking and its depiction in the modern day.